1993
DOI: 10.1063/1.352408
|View full text |Cite
|
Sign up to set email alerts
|

Microwave characterization and modelization of magnetic granular materials

Abstract: The use of dispersion techniques for development of microwave absorbers is a convenient way of realization of coatings with good attenuation characteristics in the 1- to 20-GHz range. Particularly, elastomer mixing is a very good technique for dispersion and individualization of each grain up to 60% volume. A first generation of materials, developed with ferrite powders, has been extensively studied. It was found possible to predict properties of composites with classical mixture laws using intrinsic propertie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
49
0
3

Year Published

1998
1998
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 108 publications
(53 citation statements)
references
References 7 publications
1
49
0
3
Order By: Relevance
“…The measured results are shown in Figure 10. [33,48]. The Fe 3 O 4 composites exhibit not only high dielectric loss, but also relatively large magnetic loss, suggesting that they have excellent EM absorption properties.…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…The measured results are shown in Figure 10. [33,48]. The Fe 3 O 4 composites exhibit not only high dielectric loss, but also relatively large magnetic loss, suggesting that they have excellent EM absorption properties.…”
Section: Resultsmentioning
confidence: 97%
“…On the basis of the factors above, the Fe 3 O 4 particles exhibit high dielectric loss. [33,35,48]. For example, Olmedo et al [48] investigated the complex permittivity and complex permeability of ferromagnetic particles by the extending Bruggeman method, and found that nonspherical particles showed higher ″ and ″ compared with spherical magnetic particles.…”
Section: Resultsmentioning
confidence: 97%
“…(1)) or the extended Bruggeman effective medium theory [4,9], we can not calculate the effective permeability of particle oriented-distributed composites. …”
Section: Details Of Theoretical Calculationsmentioning
confidence: 98%
“…Natural resonance frequency of NHSs is different with that of Ni nano-particle (5.2 GHz) [20] because of the presence of phosphorus. The interaction of NHSs and Co-P coatings causes that natural resonance frequency of samples lies between that of Ni nanoparticles and Co (hcp) particles (about 6.5 GHz) [23][24][25]. For the Co-P coatings and NHSs, it can be estimated that naturalresonance frequency will be around several tens of megahertz.…”
Section: Microwave Absorptive Propertiesmentioning
confidence: 99%